Identificación de la tipología de productores agrícolas en tres comunidades de la quebrada Tamshiyacu. Región Loreto. 2020 - Tello Paredes, Francis Jair (2023)
This work was carried out in the year 2020, Fernando Lores district, to identify the "typology of agricultural producers" that can be considered for this area. The results were based on the criteria made by Tico (2011), and it is concluded in aspects of land tenure, 49.23% maintain areas less than or equal to 5 hectares, with a private regime (52.31%). Likewise, family labor prevails in these agricultural properties (78.46%), where cattle breeders maintain permanent staff on their land (7.69%); They are dedicated exclusively to productive activity (92.31%), with the planting of species of bread to take (cassava and banana), vegetables (sweet pepper, cucumber, caygua, etc.), Amazonian fruit trees, regional poultry farming (a form of savings to correct any family need), cattle (9.23%) and transform cassava into fariña. The production is mostly sold in the local market (64.62%), the cattle in the city of Iquitos; they do not receive information about the prices of products in the market and they tend to find out the same in the local market or from some neighbors (93.85%), they state that they do not receive advance payments for the products to be harvested (92.31%). They did not attend any agricultural training event, only the cattle farms received this training in sanitary aspects; For the sowing of their crops they use their own seeds derived from previous harvests (83.08%), certified vegetable seeds are purchased. They use pesticides like Aldrin for their old knowledge and organic fertilizers. They generate income from agricultural activity less than or equal to S/. 700.0, which is financed with own resources. Most of them do not calculate their production costs, only 4.62% carry out this action. Executed the study, it was evidenced that the proposed general hypothesis is fulfilled and for the study these productive units are considered as small agriculture in transformation, it is fulfilled, performing for the same, the possession of lands of less than 0.5 Hectares, use of labor Family work, sale of diverse products emanating from the total agricultural activity, with low income from the activity.